2019
DOI: 10.3390/jcm8091416
|View full text |Cite
|
Sign up to set email alerts
|

Physician Adherence to Treat-to-Target and Practice Guidelines in Rheumatoid Arthritis

Abstract: Principles of treat-to-target (T2T) have been widely adopted in both multinational and regional guidelines for rheumatoid arthritis (RA). Several questionnaire studies among physicians and real-world data have suggested that an evidence–practice gap exists in RA management. Investigating physician adherence to T2T, which requires a process measure, is difficult. Different practice patterns among physicians are observed, while adherence to protocolized treatment declines over time. Rheumatologist awareness, agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 64 publications
1
25
0
2
Order By: Relevance
“…Barriers to implementing T2T principles are numerous, including treating physicians’ clinical inertia, patients’ concerns related to treatment intensification, and reimbursement of effective medications. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Barriers to implementing T2T principles are numerous, including treating physicians’ clinical inertia, patients’ concerns related to treatment intensification, and reimbursement of effective medications. 2 …”
Section: Introductionmentioning
confidence: 99%
“…The value of such an approach is better patient outcomes in both the short and long term, which in addition to remission includes reductions in comorbidities and cardiovascular risk, as well as improvements in quality of life and productivity [81,[85][86][87][88][89][90]. However, several studies have shown that the practices outlined in guidelines do not translate well into the clinic with low rates of adherence to recommendations [70,[91][92][93][94]. Reasons for nonadherence include lack of awareness of guidelines, individual physician beliefs and financial and cost issues [91][92][93], including access to the relevant treatments as outlined earlier in the review.…”
Section: Achievement and Maintenance Of Remissionmentioning
confidence: 99%
“…In addition, the majority of international guidelines restrict the use of biologics to the second line, following a ‘top-up’ approach, starting with a conventional DMARD before moving onto a bDMARD once disease progresses or does not respond to therapy [ 19 21 , 24 , 26 , 28 30 , 69 ]. A further complication is that guidelines are often not followed in clinical practice [ 70 72 ]. Furthermore, the health economic data that reimbursement criteria are based upon may not be up to date, leading to misalignment between policy and practice [ 73 , 74 ].…”
Section: Earlier Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Treat‐to‐target (T2T) regimens in RA reduce disease burden, joint damage, disability 2‐4 and mortality 5 . While an RA‐T2T approach clearly improves outcomes, implementation in clinical practice is challenging and an evidence‐practice gap has likely emerged 6,7 …”
Section: Introductionmentioning
confidence: 99%